Modelos numéricos de deformación por intrusiones magmáticas con elementos finitos (2017)
Understanding the deformation associated with magmatic intrusion can be an important tool into eruption forecasting, a very relevant and useful development in Colombia. The accuracy of these models can be increased with an adequate selection of parameters and initial conditions, and learning which of these are really relevant can help in order to get better results, numerical and analytical. In this work we propose three models, two of them taking into account heat transfer coming from the magma intrusion and the cooling of the Earth's nucleus in an elastic regime, and a third one only considering a viscoelastic regime, all of them time dependent. By an estimation of the temperature evolution using Finite Element Models in COMSOL 5.2v, we aim to understand the effects of including volume dependence (instead of a pressure one) into the Mogi equations, finally comparing with the transient viscoelastic case. For the analytical solutions of these...